2019
DOI: 10.1111/pbi.13314
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of genetic architecture for glucosinolate accumulations in leaves and seeds of Brassica napus by genome‐wide association study

Abstract: Glucosinolates (GSLs), whose degradation products have been shown to be increasingly important for human health and plant defence, compose important secondary metabolites found in the order Brassicales. It is highly desired to enhance pest and disease resistance by increasing the leaf GSL content while keeping the content low in seeds of Brassica napus, one of the most important oil crops worldwide. Little is known about the regulation of GSL accumulation in the leaves. We quantified the levels of 9 different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 71 publications
2
53
1
2
Order By: Relevance
“…There is considerable evidence that SVs control many phenotypic traits [28,36,37], and GWAS represents a powerful tool for mapping genes in genetic and molecular biology studies [19,34,35,38,39]. Due to the reliable detection of SNPs, GWAS using SNPs has been widely used; however, there are only a few studies showing that a single SNP can change gene function and the phenotype.…”
Section: Gwas Using Svs Provide a Powerful Approach For Identifying Cmentioning
confidence: 99%
See 1 more Smart Citation
“…There is considerable evidence that SVs control many phenotypic traits [28,36,37], and GWAS represents a powerful tool for mapping genes in genetic and molecular biology studies [19,34,35,38,39]. Due to the reliable detection of SNPs, GWAS using SNPs has been widely used; however, there are only a few studies showing that a single SNP can change gene function and the phenotype.…”
Section: Gwas Using Svs Provide a Powerful Approach For Identifying Cmentioning
confidence: 99%
“…4d). It has been reported that the expression of PpMYB10.1 is regulated by the BL transcription factor [38]; however, the effect of the deletion on the promoter activity of PpMYB10.1 remains unknown. In a dual-luciferase reporter assay, we found that the deletion enhanced the promoter activity, consistent with a role of PpMYB10.1 in flesh color formation around the stone (Fig.…”
Section: Gain Of Anthocyanins In Flesh Surrounding the Fruit Stonementioning
confidence: 99%
“…GSL concentration is unequally distributed throughout the plant body. For instance, in Brassica napus , the GSL concentration in the seed is greater than that in leaves [ 22 ]. This variation appears to be more relevant in root vegetable crops ( Moringacea family) than that in oilseed crops ( Brassicaceae family).…”
Section: Natural Occurrence Of Glucosinolatesmentioning
confidence: 99%
“…In order to compare the newly identified loci (SNP positions) with the loci that were previously demonstrated to be significantly associated with glucosinolate content, first, the available information on the exact physical distance of loci associated with glucosinolate content was collected from the previously published papers [24][25][26]42,43]. Second, for each SNP in the present study, the corresponding positions in the Darmor bzh assembly version 4.1 [3] were found.…”
Section: Association Mapping Snp Annotation and Loci Comparisonmentioning
confidence: 99%
“…These studies identified a number of genetic loci associated with glucosinolate content located on the chromosomes A01, A04, A06, A09, C02, C03, and C09. Following the increasing popularity of GWAS several works have been published on implementing this method to diverse rapeseed lines from global collections [24][25][26]. These approaches facilitated the identification of new loci as well as new candidate genes potentially responsible for glucosinolate content in rapeseed plants.…”
Section: Introductionmentioning
confidence: 99%